Management and closure of the open abdomen after damage control laparotomy for trauma. A systematic review and meta-analysis. Issue 2 (February 2016) - Sharrock, A.E.; Barker, T.; Yuen, H.M.; Rickard, R.; Tai, N.
Abstract: Introduction: Damage control laparotomy for trauma (DCL) entails immediate control of haemorrhage and contamination, temporary abdominal closure (TAC), a period of physiological stabilisation, then definitive repair of injuries. Although immediate primary fascial closure is desired, fascial retraction and visceral oedema may dictate an alternate approach. Our objectives were to systematically identify and compare methods for restoration of fascial continuity when primary closure is not possible following DCL for trauma, to simplify these into a standardised map, and describe the ideal measures of process and outcome for future studies. Methods: Cochrane, OVID (Medline, AMED, Embase, HMIC) and PubMed databases were accessed using terms: (traum*, damage control, abbreviated laparotomy, component separation, fascial traction, mesh closure, planned ventral hernia (PVH), and topical negative pressure (TNP)). Randomised Controlled Trials, Case Series and Cohort Studies reporting TAC and early definitive closure methods in trauma patients undergoing DCL were included. Outcomes were mortality, days to fascial closure, hospital length of stay, abdominal complications and delayed ventral herniation. Results: 26 studies described and compared early definitive closure methods; delayed primary closure (DPC), component separation (CS) and mesh repair (MR), among patients with an open abdomen after DCL for trauma. A three phase map was developed to describe the temporal and sequential attributes of each technique. Significant heterogeneity in nomenclature, terminology, and reporting of outcomes was identified. Estimates for abdominal complications in DPC, MR and CS groups were 17%, 41% and 17% respectively, while estimates for mortality in DPC and MR groups were 6% and 0.5% (data heterogeneity and requirement of fixed and random effects models prevented significance assessment). Estimates for abdominal closure in the MR and DPC groups differed; 6.30 (95% CI = 5.10–7.51), and 15.90 (95% CI = 9.22–22.58) days respectively. Reporting poverty prevented subgroup estimate generation for ventral hernia and hospital length of stay. Conclusion: Component separation or mesh repair may be valid alternatives to delayed primary closure following a trauma DCL. Comparisons were hampered by the lack of uniform reporting and bias. We propose a new system of standardised nomenclature and reporting for further investigation and management of the post-DCL open abdomen.